A circuit that integrates drive state and social contact to gate mating - Lindsey D. Salay; Doris Y. Tsao; David J. Anderson (Nature, 2025)
Abstract Internal motive states, such as sexual arousal, drive behaviour in response to social cues. However, little is known about how internal states and external cues are integrated to release appropriate behaviours at the correct moment during a social interaction, such as the transition from the appetitive to the consummatory phases of mating1,2. Here we identify a neural circuit in male mice that gates the onset of consummatory reproductive behaviours on contact with a mating partner. Stimulating MPOA Esr1∩Vgat hypothalamic neurons promotes mounting of conspecifics and three-dimensional dummy objects3. We find that such mounting depends on mechanosensory but not visual cues. Through a large-scale electrophysiological screen, we identify neurons in the subparafascicular thalamic nucleus that nonlinearly integrate medial preoptic area of the hypothalamus (MPOA) and mechanosensory input to encode contact with a potential mate. Circuit tracing and perturbations demonstrated that this conjunctive coding occurs by means of convergent disinhibition from MPOA and excitation from the spinal trigeminal nucleus. Functional manipulations and calcium recordings showed these social-contact neurons, marked by parathyroid hormone 2, were essential for and able to promote mounting. These data indicate that subparafascicular thalamic nucleus-parathyroid hormone 2 neurons integrate internal drive with social touch to trigger mounting at opportune moments during mating. More generally, our findings uncover a brain mechanism whereby an internal state can attribute a social quality to a generic touch to initiate purposeful reproductive actions.